Energy systems for climate change mitigation: A systematic review. (1st April 2020) - Kang, Jia-Ning; Wei, Yi-Ming; Liu, Lan-Cui; Han, Rong; Yu, Bi-Ying; Wang, Jin-Wei
Highlights: This study learns energy systems for climate mitigation from a systematic review. Heterogeneity of energy system research is summarized for the first time. A novel hand-coding typology analysis for energy systems is proposed. Abstract: The energy supply sector is the largest contributor to global greenhouse gas emissions. A good understanding of energy systems from existing research will provide multidimensional insights for appropriate actions against global warming. This study conducts a systematic review of the literature covering 1, 184 articles on energy issues dealing with climate change mitigation. Using a novel hand-coding typology analysis, we characterize the body of knowledge and identify possible research gaps according to the heterogeneity of the energy process, time scale, geographic location, energy technology, and concerned end-use sector. We find that research interest mainly focuses on the energy supply (496 papers) and the end-use process (359 papers). Energy storage and the energy–water–land nexus are two emerging areas. Biomass, solar, wind, and nuclear energy are the technologies that attract the most attention, while interest in hydrogen energy production and waste-to-energy has grown very recently. The cost-benefit and mitigation potential of renewable generation are the most studied topics, followed by the impacts of climate change on electricity production. In contrast, little attention is paid to research on traditional oil and gas exploration. Regarding the end-use sector, residents and transport are the most evident sectors studied. China, the United States, and Europe are the most featured regions while very few studies focus on Africa, South America, and Small Island Developing States. Current research topics concentrate on how to maximize the co-benefit of greenhouse gas mitigation and eco-environment protection via cost-benefit reinventions of energy systems. Discussions of technological innovation are grounded in optimal technology portfolio deployment and cost reduction potential, along with financial and political incentives.